STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA DI MTs NEGERI 1 KARANGANYAR - Susiloningsih, Susiloningsih; Munadi, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Madrasah that excel have a vision and mission to improve the quality of education. The principal of the madrasah has a big influence in improving student academic achievement. The purpose of this study was to determine the transformational leadership strategies of madrasah principals in an effort to improve academic achievement of students at MTs Negeri 1 Karanganyar. This research is a case study research. Test the validity of the observation data using triangulation of sources and methods, data analysis techniques using qualitative data analysis. The results showed that the principal has a goal to improve student academic achievement. Based on the research, it can be concluded that the principal of the madrasa has the perspective that student academic achievement is the vision and mission of the madrasa. The strategy carried out by the head of the madrasa is to determine the goal, namely to conduct an evaluation to determine the vision and mission of the madrasa. Growing people or staff, is done by facilitating teachers to improve their competence, Rearranging the organization by collaborating with the external environment of the madrasa and creating a climate of collaboration within the madrasa's internal environment, building instructional programs such as holding superior class program classes, empowering MGMP, conducting activity evaluations and conducting routine coordination.